Penilaian ujian respons auditori keadaan mantap di kalangan subjek berpendengaran normal dan bermasalah pendengaran sensorineural - Nashrah Maamor,; Sitti Ladyia Salleh,; Nurul Ain Abdullah, (penerbit ukm, 2005)
The objective of this study was to investigate the degree to which Auditory Steady State Response (ASSR) thresholds correlate with behavioral thresholds in two groups of adult subjects, one with normal hearing and the other with sensorineural hearingimpairment. When the relationship between ASSR and behavioral thresholds were analyzed separately according to different groups of subjects, significant correlations were only found for the hearing impaired group. The mean differences between the actual and the predicted thresholds derived from linear regression analysis for that group of subjects were found to be 5 dB (SD = 4), 3 dB (SD = 3), 4 dB (SD = 3) and 4 dB (SD = 4) with correlation coefficients of 0.80, 0.88, 0.91 and 0.97 for the 500, 1000, 2000 and 4000 Hz carrier frequencies, respectively. When the relationship between ASSR and behavioral thresholds were analyzed using data from both groups of subjects, correlation coefficients were found to be higher across carrier frequencies of 500 to 4000 Hz (r ³ 0.96) with mean differences between the actual and the predicted thresholds of 6 dB (SD = 3), 4 dB (SD = 3), 4 dB (SD = 3) and 6 dB (SD = 3) for the hearing impaired group and 11dB (SD = 7), 8 dB (SD = 8), 8 dB (SD = 6) and 10 dB (SD = 7) for the normal hearing group. However, it was observed that the range of differences between the actual and the predicted thresholds were quite large reaching 34 dB for the 500 and 4000 Hz carrier frequencies. This suggests that in clinical setting, ASSR cannot predict the presence or absence of a hearing loss accurately. In general, it can be concluded that ASSR allow for an accurate prediction of behavioral thresholds within ± 10 dB in subjects with hearing impairment. However, ASSR cannot accurately predict hearing thresholds in normally hearing individuals.